Bir Teknik Sokratik Sorgulama ile Yönlendirilmiş Keşif - Türkçapar, M Hakan; Kahraman, Melis Sedef; Sargın, A Emre (My University, 2015)
Sokratik yöntem, antik dönem Yunan filozofu Sokrates'in felsefi düşünüşü ve bilgiyi soru sorarak öğretme yöntemidir. Sokrates'in öğrencilerine bilgileri sorular sorarak öğretmesi Sokratik dialog adıyla bilinir. Bu anlamda sokratik sorgulamayla aslında karşısındakine yeni bir şey öğretilmemekte sadece bilinen anımsatılmakta ve tekrar bulunmaktadır. Bilişsel davranışçı terapi sürecinde kullanılan Sokratik süreç ve bunun terapideki uygulama biçimi ise yönlendirilmiş keşif (Guided Discovery) olarak adlandırılır. Yönlendirilmiş keşif için pek çok farklı teknik kullanılabilir ancak Sokratik sorgulama en sık kullanılan ve en etkin tekniklerden bir tanesidir. Bu yöntemle bir seri soru ile aslında danışanın bilebileceği ancak farkında olmadığı bilginin farkına varmasını amaçlanır. Sokratik sorgulama danışanın iyi dinlenmesinden ve yansıtmadan faydalanılarak sorun tanımlanması, inceleme, değerlendirme yaparak alternatifler bulma, açığa çıkan yeni bilgilerin kullanılarak yeniden tanımlama yapmak ve son olarak da eski çarpık inancın sorgulanması ve yeni bilgi ışığında bir sonuca varma ve uygulama aşamalarından oluşur. Bu aşamalar esnasında kullanılan soru tipleri bilgi edinmeye dönük sorular, çeviri soruları, yorum soruları, geçmişteki benzer durumlara ilişkin uygulama soruları, analiz soruları ve analitik sentez sorularıdır. Bu yazıda Sokratik Sorgulama-Yönlendirilmiş Keşfin bu aşamaları örnek görüşmeler üzerinden gözden geçirilecektir.

Guided Discovery with Socratic Questioning "The Socratic method" is a way of teaching philosophical thinking and knowledge by asking questions. It was first used by in ancient times by the Greek philosopher Socrates who taught his followers by asking questions; these conversations between them are known as "Socratic dialogues". In this methodology, no new knowledge is taught to the individual; rather, the individual is guided to remember and rediscover what was formerly known through this process. The main method used in cognitive therapy is guided discovery. There are various methods of guided discovery in cognitive therapy. The form of verbal exchange between the therapist and client which is used during the process of cognitive behavioral therapy is known as "socratic questioning". In this method the goal is to make the client rediscover, with a series of questions, a piece of knowledge which he could otherwise know but is not presently conscious of. The Socratic Questioning consists of several steps, including: identifying the problem by listening to the client and making reflections, finding alternatives by examining and evaluating, reidentification by using the newly rediscovered information and questioning the old distorted belief, and reaching a new conclusion and applying it. Question types used during these procedures are: questions for collecting information, questions revealing meanings, questions revealing beliefs, questions about behaviours during similar past experiences, analytic questions and analytic synthesis questions. In order to make the patient feel understood, it is important to be empathetic and summarize the problem during the interview. In this text, steps of Socratic Questioning-Guided Discovery will be reviewed with sample dialogues provided for each step
Guided Discovery with Socratic Questioning
Keywords: Psikiyatri